2016
DOI: 10.1080/17461391.2016.1149227
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the relationship between biomechanics and performance of young sprinting swimmers

Abstract: The aim of this study was to compute a swimming performance confirmatory model based on biomechanical parameters. The sample included 100 young swimmers (overall: 12.3 ± 0.74 years; 49 boys: 12.5 ± 0.76 years; 51 girls: 12.2 ± 0.71 years; both genders in Tanner stages 1-2 by self-report) participating on a regular basis in regional and national-level events. The 100 m freestyle event was chosen as the performance indicator. Anthropometric (arm span), strength (throwing velocity), power output (power to overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Swimming kinematics is associated with anthropometric characteristics in the front crawl as evidenced by the results of studies conducted in youth swimmers ( Morais et al, 2012 , 2013 ; Maszczyk et al, 2012 ; Stanula et al, 2012 ). In those and further studies of Morais et al (2016) and Barbosa et al (2015) , it was shown that a significant relationship existed between the arm span and propelling efficiency or performance in youth swimmers. In our study conducted in junior and youth swimmers, a relationship between limb length and SL was not found; and other somatic traits (body length, length of upper and lower extremities) did not reveal an impact on VSBF, but according to the literature on the subject (Bulgakova, 1978, cited in: Chollet, 1990 ) competitive butterfly swimmers are not as tall as backstrokers or sprint freestyle swimmers, although the amount of data on this issue is scarce.…”
Section: Discussionmentioning
confidence: 89%
“…Swimming kinematics is associated with anthropometric characteristics in the front crawl as evidenced by the results of studies conducted in youth swimmers ( Morais et al, 2012 , 2013 ; Maszczyk et al, 2012 ; Stanula et al, 2012 ). In those and further studies of Morais et al (2016) and Barbosa et al (2015) , it was shown that a significant relationship existed between the arm span and propelling efficiency or performance in youth swimmers. In our study conducted in junior and youth swimmers, a relationship between limb length and SL was not found; and other somatic traits (body length, length of upper and lower extremities) did not reveal an impact on VSBF, but according to the literature on the subject (Bulgakova, 1978, cited in: Chollet, 1990 ) competitive butterfly swimmers are not as tall as backstrokers or sprint freestyle swimmers, although the amount of data on this issue is scarce.…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, Tanaka et al (1993) and Trappe and Pearson (1994) found increases in strength throughout a season with a dryland strength program, but did not observe any increases in swimming performance (Tanaka, Costill, Thomas, Fink, & Widrick, 1993;Trappe & Pearson, 1994). Trappe and Pearson (1994) It is highly controversial whether an increase in dryland strength will necessarily translate to improved sprint swimming performance, especially in a younger population (Crowley et al, 2017;Garrido et al, 2010;Morais et al, 2016;Schumann & Rønnestad, 2019). Swimmers not only have to develop high levels of force, but must also apply them in an effective way to maximize propulsion (Crowley et al, 2017).…”
Section: Strength Training In Swimmingmentioning
confidence: 99%
“…Instead, no improvements were found in the previous study [10] being reported similar improvements in swimming velocity gains between experimental and control group (4.8 vs. 3.2%, respectively). The lack of studies may be due to financial and ethical issues [29] or the assumption by coaches that technical training is more important than S&C training [8,10,28,30]. Coaches usually assume that muscular hypertrophy and consequent decreases in flexibility may affect the swimmer's ability and increase drag forces [5].…”
Section: Effects Of Sandc On Swimming Performance According To Agementioning
confidence: 99%
“…In fact, few studies have focused on youth swimmers [1,9,10,13,16,26], perhaps because of ethical issues [28]. Nevertheless, S&C and in waterpower output seem to have a determinant influence on youth swimmers' performance and should be part of their training [29].…”
Section: Introductionmentioning
confidence: 99%